Spontaneous Intracranial Hemorrhage (SICH) Concomitant with Subarachnoid and Subdural Hemorrhage: Case Report - Dani Osman; Etienne El-Helou; Baha’eddin A. Muhsen (Dr. Sulaiman Al Habib Medical Journal)
Spontaneous intracranial hemorrhage (SICH) represents a critical medical condition that requires timely diagnosis and intervention due to its association with severe clinical outcomes. The coexistence of SICH alongside other forms of intracranial bleeding, such as subdural hematoma (SDH) and subarachnoid hemorrhage (SAH), adds complexity to both its clinical presentation and management strategies. This atypical presentation, particularly due to its resemblance to ruptures associated with aneurysmal or arteriovenous malformations, underscores the necessity for a comprehensive diagnostic evaluation and careful consideration of a broad spectrum of differential diagnoses. A 67-year-old previously healthy female presented with spontaneous intracranial hemorrhage involving multiple bleeding subtypes, including left temporal SICH, SAH, and SDH. Given the severity of the condition and imminent risk of impending brain herniation, surgical intervention was undertaken, comprising craniotomy and tubular evacuation. The coexistence of SICH with SAH and SDH in uncommon locations, such as the temporal lobe, presents a unique and challenging clinical scenario. Their simultaneous occurrence warrants thorough investigation and meticulous management. In select cases, minimally invasive surgical interventions may be employed to address severe symptoms, large hematoma volumes with midline shift, and peri-hemorrhagic brain edema. The primary goal of such interventions is to reduce morality while achieving an acceptable functional outcome.